Theranostic Bioabsorbable Bone Fixation Plate with Drug‐Layered Double Hydroxide Nanohybrids. Issue 21 (10th October 2016) - Kim, Myung Hun; Hur, Woojune; Choi, Goeun; Min, Hye Sook; Choi, Tae Hyun; Choy, Young Bin; Choy, Jin‐Ho
Abstract : A bioabsorbable polymeric bone plate enabled with both diagnostic and therapeutic functionalities (radiopacity and sustained drug release, respectively) is proposed. To this end, a drug–inorganic nanohybrid (RS‐LDH) is examined as a theranostic agent by intercalating an anti‐resorptive bone remodeling drug, risedronate (RS) into a layered double hydroxide (LDH) via an ion‐exchange reaction. The RS‐LDH is prepared as a sheet with a biodegradable polymer, poly(lactic‐ co ‐glycolic acid), and is then attached onto the clinically approved bioabsorbable bone plate to produce the theranostic plate. Because of the presence of the metals in the LDH, the theranostic plate results in discernible in vivo X‐ray images for up to four weeks after implantation. Concurrently, bone regeneration is also significantly improved compared with the other control groups, likely because of this material's sustained drug‐release property. The theranostic plate is also largely biocompatible, similar to the plate already approved for clinical use. It is concluded that the combination of a biodegradable bone plate with RS‐LDH nanohybrids can constitute a promising system with theranostic ability in both X‐ray diagnosis and expedited bone repair. Abstract : The combination of a biodegradable bone plate with a theranostic sheet containing risedronate, an anti‐resorptive bone remodeling drug, intercalated layered double hydroxide nanohybrid as a theranostic agent, and poly(lactic‐ co ‐glycolic‐acid) as a binder can constitute a promising system with theranostic ability in both X‐ray diagnosis and expedited bone repair.